How Suppressed Anger Can Become an Illness: A Qualitative Systematic Review of the Experiences and Perspectives of Hwabyung Patients in Korea - Suh, Hyo-Weon; Lee, Ki-Beom; Chung, Sun-Yong; Park, Minjung; Jang, Bo-Hyoung; Kim, Jong Woo (Frontiers in Psychiatry, 2021)
Background: In the clinical field, anger has generally been studied in terms of aggressive behavior. However, in Asians, anger suppression is more common than anger expression. Hwabyung is a culture-related anger syndrome in Korea and is known to occur due to the continued repression of anger. Investigating Hwabyung should lead to a better understanding of the multiple dimensions of anger. To explore Hwabyung patients’ experiences and perspectives, a meta-aggregation approach was used to conduct a systematic review and a qualitative synthesis. Methods: A systematic search was conducted in MEDLINE/PubMed, EMBASE, Allied and Complementary Medicine Database (AMED), Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycARTICLES, and four Korean databases (Korean Medical Database (KMbase), Korean Studies Information Service System (KISS), National Digital Science Library (NDSL), and Oriental Medicine Advanced Searching Integrated System (OASIS)) in September 2020. Studies were included if they collected and analyzed qualitative data from Hwabyung patients. Qualitative research findings on the experiences and perspectives of Hwabyung patients in Korea were critically appraised and synthesized using the Joanna Briggs Institute methodology. Results: Seven eligible studies were included. The findings from those studies (i.e., theme or subtheme of qualitative research) were aggregated into categories (a group of similar findings) and synthesized findings (a group of categorized findings). Ultimately, 116 findings were aggregated into 15 categories. Finally, four synthesized findings were derived from the 15 categories: (i) anger arousal, (ii) blame, (iii) uncontrollable physical and emotional symptoms, and (iv) compromise and temporary coping. Conclusions: Patients with Hwabyung experience chronic anger through the complex cognitive processes involved in blame. Hwabyung negatively affects patients’ physical, psychological, and social functions. Because Hwabyung patients feel as if they are losing control, due to emotional dysregulation and physical symptoms, professional support should be provided to facilitate their coping strategies. Further studies on Hwabyung can serve as a new model of pathological anger.